Profiles of alkali concentration and galactoglucomannan degradation in kraft impregnation of Scots pine wood: Experimental observations and modeling - Montagna, Pablo Nicolás (2015)
A deep understanding of alkali impregnation including the profiles of alkali concentration and hemicellulose degradation is necessary to analyze the optimization of current and innovative processes. In this paper, the impregnation of Scots pine (Pinus sylvestris L.) wood is analyzed and modeled under consideration of deacetylation, reactions of acidic group, and galactoglucomannan (GGM) degradation. The immobile anionic groups activated by the ionization of lignin-derived OH groups are also considered for the assessment of the Donnan effect. Predicted profiles of sodium and hydroxide ions and acetyl group concentrations are compared to experimental results. The balance between impregnation and hemicellulose degradation levels is discussed based on the developed models. Expectedly, higher concentrations and temperatures speed up the impregnation process. Nevertheless, a higher OH-concentration has two benefits for the same impregnation front position – the alkali charge inside the chip is higher and the GGM degradation is lower.